AndiLearn (Android Interactive Learning) in Project-Based Activities to Strengthen Pancasila Student Profiles and Enhance Student Digital Literacy - Riawan Yudi Purwoko; Latifah Nur Ahyani; Jayanti Putri Purwaningrum; Hasan Basri; Wiwit Agus Triyanto (Universitas Pendidikan Ganesha, 2025)
The problem currently encountered is low student literacy, which makes it difficult for students to understand the material. This research aims to develop teaching materials in the form of AndiLearn (Android Interactive Learning) in project activities to strengthen the profile of Pancasila students to increase the digital literacy of phase B class students at SD N Sindurjan in the Independent Curriculum. This type of research and development is R&D (Research and Development) research using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. These five stages are implemented by analyzing needs, student characteristics, and the curriculum. Validation of AndiLearn (Android Interactive Learning) in project activities to strengthen the profile of Pancasila students was carried out by language experts, learning media, and driving school facilitators, practicality was seen based on teacher and student responses. The results of the development of AndiLearn (Android Interactive Learning) in the project activities to strengthen the profile of Pancasila students to increase the digital literacy of phase B class students at SD N Sindurjan were declared very valid and practical. Based on the results from the validator, an average validity of 89% was obtained, namely in the very valid category, and the practicality results obtained an average of 88.87% in the very practical category. Therefore, it can be concluded that the AndiLearn (Android Interactive Learning) created can be valid and practical to be used during the Strengthening Pancasila Student Profile Project activities to implement Independent Curriculum learning.